Halogen bonding driven crystal engineering of iodophthalonitrile derivatives. Issue 27 (18th June 2018) - Ateş, Özge Dilara; Zorlu, Yunus; Kanmazalp, Sibel Demir; Chumakov, Yurii; Gürek, Ayşe Gül; Ayhan, Mehmet Menaf
Abstract : Various halogen bonding driven crystal structures can be obtained by simple modifications of iodophthalonitrile derivatives. Abstract : The nature of halogen bonds (XBs) depending on the number and position of the XB donor (I) and acceptor (CN) groups in iodophthalonitrile derivatives such as 4-iodo-phthalonitrile (2a ), 3-iodo-phthalonitrile (2b ), 4, 5-diiodo-phthalonitrile (2d ) and 3, 4-diiodo-phthalonitrile (2c ) as well as in para -, ortho - and meta -iodo-substituted benzonitriles (1a–1c ) was studied by X-ray analysis and ab initio calculations. Density functional theory (DFT) and the Boltzmann transport equation have been applied to calculate the semi-classical thermoelectric transport properties of the crystalline compounds of1a–1c, 2a–2d . In2a–2c, the molecules are consolidated into 2-D networks while in2d the triple helix spiral staircase structure is formed due to XBs where the unusual bifurcated asymmetric XBs were observed. The Seebeck coefficients of all the studied organic semiconductors were significantly positive, suggesting that the hole-type carriers dominate the thermoelectric transport.